Plant remains found in grave No. 8 at Sárrétudvari-Őrhalom: An archaeobotanical report - Torma, Andrea (Communicationes Archaeologicae Hungariae, 2006)
Plant remains found in grave No. 8 at Sárrétudvari-Őrhalom: An archaeobotanical report